Best European fiction 2011 - Hemon, Aleksandar, 1964- (Champaign [Ill.] : Dalkey Archive Press, 2010)
Collects fourty short stories by both established and lesser-known authors from fourty European countries, including Antonio Fian, Alasdair Gray, and Victor Pelevin.
Includes bibliographical references.
Publisher's Weekly
Adult.
Adult
Keywords: Short stories, European; Short stories